Sex Differences in Rhesus Monkeys’ Digit Ratio (2D:4D Ratio) and Its Association With Maternal Social Dominance Rank - Baxter, Alexander; Wood, Elizabeth K.; Jarman, Parker; Cameron, Ashley N.; Capitanio, John P.; Higley, J. Dee (Frontiers in Behavioral Neuroscience, 2018)
Prenatal androgen exposure (PAE) plays a pivotal role in masculinizing the developing body and brain. One commonly used biomarker for PAE is the pointer-to-ring-finger digit length (2D:4D) ratio. Although this biomarker is sexually dimorphic across many primate species, data suggest that sexual dimorphism in 2D:4D ratio may be in the opposite direction in some monkey species, when compared to the pattern exhibited by humans and great apes. Using a large sample size, we investigated whether rhesus macaques’ (Macaca mulatta) 2D:4D ratio shows the same sex-differentiated pattern present in other Old World monkey species. We also investigated whether individual differences in 2D:4D ratio are associated with the social dominance rank of subjects’ mothers during pregnancy, and the social dominance rank the subjects attained as adults. Subjects were 335 rhesus monkeys between 3-24 years of age (M = 6.6). Maternal dominance rank during pregnancy and subjects’ adult dominance rank were categorized into tertiles (high, middle, and low). Results show that, on both hands, male rhesus monkeys exhibited higher 2D:4D ratio than females, a pattern consistent with other monkey species, and a reversal from the pattern typically observed in humans and apes. This sex difference was modulated by maternal dominance rank, with sex differences in right-hand 2D:4D ratio most pronounced in subjects born to low-ranking mothers, indicating that maternal dominance rank during pregnancy may influence levels of PAE. There was also an association between subjects’ right-hand 2D:4D ratio and the dominance rank they attained as adults, with high- and low-ranking subjects exhibiting lower 2D:4D ratio than middle-ranking subjects. These findings show a consistent sex difference in Old World monkeys’ 2D:4D ratio that diverges from the pattern observed in apes and humans and suggest a complex association between PAE and social dominance rank in rhesus monkeys.